Effect Of Herringbone Technique On Students’ Reading Comprehension In Narrative Text - Niswa, Khairun; Kristina Sinaga, Yanti (Journal of Social Science and Humanities Research, 2022)
The research aimed to find out the effect of Herringbone Technique on students’ reading comprehension at grade eight of SMP Negeri 7 Pematangsiantar. There are also several main theories used to support this research, namely; Brassel and Rasinski (2008), Cahyono et. al. (2011), Deegan (2006), Pang et. al. (2003), Patel and Jain (2008), Richards and Renandya (2002), Sweet and Snow (2003). This research was designed as a quantitative method with quasi-experimental research design. Eight students’of 4 and 5 were selected as the participants. The experimental class was treated using Herringbone Technique while the control class was not treated using Herringbone Technique. The data were obtained through pre-test, treatment, and post-test. The pre-test was held to know the students’ basic ability or score before treatment was given. Meanwhile, the post test was held to know the students’ achievement and significant effect after the students’ were taught using Herringbone Technique. The data shows that the difference or the improvement as the whole students’ got in post test from control to experimental group is 345 or 11,5 point in average. The score of t-test (7,17) is higher than t-table (1,67) at the level of significance 5% for two tailed test, so Alternative Hypothesis is accepted and Null Hypothesis is rejected. Finally, by knowing the result, it is better if English teachers apply Herringbone Technique to improve the students’ achievement on reading comprehension.